Equi-protein Replacement of Fishmeal with Leucaena Leaf Protein Concentrate: An Assessment of Performance Characteristics and Muscle Development in the Chicken - Agbede, Johnson O. (International Journal of Poultry Science, 2003)
A batch of three hundred 7- day old Shaver broiler-chicks was used to assess the equi-protein replacement of fishmeal (FM) protein with Leucaena leaf protein concentrates (LLPC) in broiler-starter mash. Before the feeding trial, the LLPC was analyzed for its protein, amino acids, phytin and tannin contents. Thereafter, five diets were tested. The control (diet 1) had 5% FM protein whose protein was gradually replaced at 25, 50, 75 or 100% with LLPC in diets 2 to 5. Thus the inclusion level of LLPC was 2.24, 4.48, 6.72 or 8.96%, respectively for diets 2 to 5. The chicks were randomly assigned in triplicate of 60 chicks per dietary treatment. The average weight gain (AWG), average feed consumption (AFC) and feed conversion ratio (FCR) of chicks fed the control diet were significantly (P<0.05) higher than those fed the LLPC-based diets. The AWG of the broilers fed on the control diet decreased to 80.6% in chicks fed 2.24% LLPC-based diet and to 39.3% in chicks fed 8.96% LLPC based diet with a corresponding decrease of AFC by 88.6 and 62.9%, respectively. Nitrogen retention (NR) of chicks fed the control diet and those fed 2.24, 4.48 or 6.72% LLPC-based diets were similar. At the close of the feeding trial, the chicks were slaughtered for carcass traits, relative organ and muscle measurements as well as blood and serum analyses. Only the weights of the chest, belly fat, spleen, pancreas and gizzard were significantly (P<0.05) different. The weight of chest and belly fat decreased with increased FM protein substitution with LLPC while the relative weight of gizzard increased with increased LLPC substitution for FM protein. The relative weight, length and breadth of the Supra coracoideus, Pectoralis thoracicus and Gastrocnemius of chicks fed the control diet and those fed LLPC-based diets were similar. The blood variables and the total serum protein (TSP) of the chicks fed the control diet were not significantly (P>0.05) different from those fed the LLPC-based diets. In the main, the use of 2.24% LLPC in broiler-chick diets, especially in region with limited supply of fishmeal, in a complementary fashion with other ingredients rich in the limiting essential amino acids (EAAs) is suggested.